Civil Engineering Materials - Dhir Ravindra K; Jackson Neil; Macmillan (1996)
This book will appeal to undergraduate and equivalent students of Civil Engineering, Construction Technology, Architecture and related disciplines. Preface, Acknowledgements, Introduction, Metals, Structure of Metals, Deformation of Metals, Strengthening Mechanisms, Behavior in Service, Metallic Materials in Constructions, Timber, Structure of Wood, Production of Solid Timber Sections, Durability of Timber, Properties and Uses of Solid Timber, Processed Timber Products, Concrete, Constituent Materials, Properties of Fresh Concrete, Properties of Hardened Concrete, Concrete Durability, Assessment of in Situ Concrete Quality, Concrete Mix Design and Quality Control, Bituminous Materials, Bituminous Binders, Properties of Bitumen - Aggregate Mixes, Designs of Bitumen - Aggregate Mixes, Soils, Bulk Properties, Water in Soils, Shear Strength of Soil, Engineering Applications, Polymers, Polymer Technology, Bricks and Blocks, Clay Brick, Concrete Block, Index.